(untitled) (Islamic Sciences Journal, 2024)
My research, entitled: (Adding insect flour to foodstuffs - a comparative jurisprudential study), is one of the emerging topics at the present time, as the use of insect flour and its addition to food materials has recently appeared. The European Union has approved new laws that allow the use of these insects as food for people of the Union countries. The research included an introduction, a preface, two topics, a conclusion and results. As for the introduction, it includes the importance of the topic, the reason for choosing the topic and its purposes. It included also, how to add insect flour, its types, and the countries that do this. As for the first requirement: it included the legal ruling on eating insects. As for the second requirement: it included the legal ruling on adding insect flour to foodstuffs. The study comes finally with the most important findings and recommendations.